Sistem Automasi Reporting Management Employee Stock Option Plan (MESOP) Berbasis Website - Rohman, Reza Fadilah; Wulandari, Asri; Yusantina Calvianty, Intan (Jetri : Jurnal Ilmiah Teknik Elektro, 2024)
Management Employee Stock option Plan (MESOP) is an incentive scheme that grants employees the right to purchase company shares at a predetermined price. In its implementation, reporting is necessary to monitor the movement of employee stock option transactions. ESOP reporting is designed with automation adoption to enhance efficiency, accuracy, and time savings. The evaluation of ESOP reporting automation is conducted by analyzing ESOP reporting results and applying the Overall Equipment Effectiveness (OEE) method to measure Availability Rate, Performance efficiency, and Product Quality. The results of the ESOP reporting evaluation analysis conclude that the identification of employee transaction data from the 'Employee Transaction List' page aligns with the results generated by the ESOP reporting automation system on the 'Report' page. In the performance of ESOP reporting with automation, an Availability Rate of 100% is achieved. Furthermore, for Performance efficiency, ESOP reporting with automation reaches a value of 99.6% compared to manual reporting. Meanwhile, for Product Quality, ESOP reporting with both automation and manual methods obtains a value of 100%. The conclusion drawn from the obtained OEE value is 99.6%, surpassing the expected World Class OEE standard of around 85%.